Differences in the Effectiveness of Health Promotion through Video and Interactive Dialogue on Smoking Cessation Interest Among Teenagers in Palembang - Vondy Holianto (Community Medicine and Education Journal, 2021)
Cigarettes have long been recognized as a risk factor for various health problems, and are the world's largest preventable cause of death1. Teenagers are more easily influenced especially by social groups to do negative things, such as smoking2. Currently the trend to start smoking is increasing among teenagers. This study aims to compare the effectiveness of health promotion presented in the form of audio-visual and interactive dialogue on interest in quitting smoking in teens in Palembang. This research is an analytic study through a quasi-experimental approach with a pretest-posttest two group research design without control group. The research sample consisted of 206 teenage smokers, divided into 2 groups, namely 103 teenage in the video group and 103 teenage in the interactive dialogue group. This study uses paired t-test, Wilcoxon, and Mann Whitney test. This study reveals that health promotion through video media and interactive dialogue is effective to elevate the knowledge and interest in smoking cessation among teenagers (p = 0.000 α = 0.05). The mean value of knowledge and interest in the interactive dialogue group is higher than in the video group. However, there was no difference concerning effectiveness of health promotion through interactive dialogue and videos on the knowledge and interest in quitting smoking among teenagers. (p = 0.21 α = 0.05).